2022
DOI: 10.1101/2022.10.31.22281766
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of mRNA COVID-19 vaccine booster doses against Omicron severe outcomes

Abstract: Background: To inform planning for further booster doses of COVID-19 vaccines, we estimated the effectiveness of monovalent mRNA vaccines against Omicron-associated severe outcomes in adults over time. Methods: We used a test-negative design and multivariable logistic regression to estimate vaccine effectiveness (VE; 2, 3, or 4 doses compared to unvaccinated individuals) and marginal effectiveness (3 or 4 doses compared to 2 doses) against Omicron-associated hospitalization or death among community-dwelling ad… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Covid-19 vaccination policies recommending the bivalent mRNA-booster vaccines as a fourth dose are mainly supported by studies on immunogenicity where some have shown higher induction of antibody levels against omicron subvariants including BA.4-5 compared with monovalent boosters. [4][5][6][7][8] Previous observational effectiveness studies of fourth dose monovalent vaccination, primarily on data from before BA.4-5 subvariant predominance, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] also lend some indirect support to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Covid-19 vaccination policies recommending the bivalent mRNA-booster vaccines as a fourth dose are mainly supported by studies on immunogenicity where some have shown higher induction of antibody levels against omicron subvariants including BA.4-5 compared with monovalent boosters. [4][5][6][7][8] Previous observational effectiveness studies of fourth dose monovalent vaccination, primarily on data from before BA.4-5 subvariant predominance, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] also lend some indirect support to these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Previous observational studies of fourth doses are primarily limited to the monovalent mRNA Covid-19 vaccines and mainly during periods prior to the emergence of the current predominating omicron subvariants BA.4 and BA.5. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] As such, data on the effectiveness of the bivalent mRNA-vaccines are needed to guide Covid-19 vaccination policy and to evaluate the benefit of developing variant-adapted Covid-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…However, a caveat is that nearly all data used to estimate the long-term VE of the second booster against severe disease came from the same study among elderly residents of long-term care facilities in Ontario, Canada. 61 In addition, this long-term VE is against BA.1 and BA.2, the dominant subvariants during the study period of 31 Dec 2021 to 27 April 2022, according to the Ontario Ministry of Health.…”
Section: Discussionmentioning
confidence: 85%
“…After removing duplicates, 1,236 articles remained, of which 116 were considered relevant after inspection of the title, abstract, and keywords. These 116 relevant articles were then reviewed in full text for eligibility, and 11 articles 23,37,[54][55][56][57][58][59][60][61][62] with 46 VE estimates were finally included in this meta-analysis (supplementary materials p 19). More summary details and detected publication bias of the included studies are given in the supplementary materials (p 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study data is divided in two periods of the COVID-19 pandemic which correspond to the period before and after Omicron as it has been shown that in pre-Omicron vaccines, the efficacy against Omicron infection is comparatively lower than that observed for Delta and Alpha strains. Furthermore, the effectiveness of these vaccines in preventing Omicron infection tends to diminish at a faster rate over time (63,64). According to the WHO, 63% of the total Mexican population has a complete primary series of COVID-19 (65).…”
Section: Introductionmentioning
confidence: 99%